Serapilheira e estoque de carbono ao longo de um gradiente altitudinal na floresta ombrófila densa, no Parque Nacional do Caparaó, ES - Castro, Kallil Chaves (2014)
This study aimed to characterize soil fertility, intake, accumulation and rate of litter decomposition in Caparaó National Park. The studies of soil fertility and litter were conducted on seven plots (20x50 m), distributed along an altitudinal gradient. Soil sampling for chemical characterization was performed at four depths (0-05, 05-10, 10-20 and 20-40 cm) and the quantification of carbon stock was held at 0-10 cm. A composite soil sample was withdrawn by depth and plot and the soil sampling was performed in November/2012. The comparison between plots was performed by U Mann-Whitney test, and Pearson Correlation was conducted to verify the interaction of attributes and carbon stock with the altitude of the plots. The quantification of the intake of litter was carried through eight collectors with an area of 0.5625 cm², systematically distributed in plots. Quantification of the accumulation of litter was performed using a template with 0.0625 cm² area, launched in zigzag on forest floor, being collected the material present inside the template. The litterfall was separated into leaves, twigs+bark, and Miscellaneous. The material was dried in an oven with forced air circulation at 65 °C for 72 hours, weighed on an analytical balance with precision 0.001g estimated at kg ha-1 . Samples were collected monthly between November 2012 and October 2013, a total sample of year. The rate of litter decomposition for the year of study and for each month of collection was calculated from the biomass of litter produced and accumulated. Analysis of variance was performed (p <0.05), and when significant, the Friedman test (p <0.05) was applied for comparison between the months (p < 0.05), and the Kruskal -Wallis test (p < 0.05) to compare the means of plots. We used the Pearson correlation to analyze the interaction between production, accumulation and decomposition of litter with climate variables, soil chemical properties and altitude of the plots, being tested by t (p > 0.05). In Chapter 1 it can be observed that the soils of the study area are acidic and low fertility. The carbon content and MO were positively correlated with the altitude of the plots, and carbon stocks did not differ significantly between plots. In Chapter 2, the results demonstrate a litterfall production to the forest in a study of 7,428.29 kg ha-1 yr-1 . Leaves represent 61.95% 11 of the annual production, the Branches 25.76 % and 12.29% Misc. The mean accumulation of litter on the forest floor was 7,246,26 kg ha-1 yr-1 , decomposition rate (k) of the material produced and accumulated in the forest was 1.03, and the mean turnover time of 50% (T50%) of the material was 246.75 days. Both entry and accumulation of litter demonstrated a seasonally not defined for the studied forest